INVESTIGATION OF PB, ZN, MN, NI, CO AND CR IN INSOLUBLE DUSTFALL - Khan, Farid Ullah; Shakila, B; Jehangirb, S; Ashfaq, M (Biological Sciences - PJSIR, 2003)
Dust samples collected from different locations in urban areas of Peshawar were analyzed for lead, zinc, manganese, nickel, cobalt and chromium using atomic absorption spectrophotometric technique. Elemental concentrations of the stu- died elements did not vary significantly at different sample locations. A comparison of the elemental contents with the local soil was also made. Soil, road dust, vehicle exhaust, metallic corrosion, tire wear, zinc compounds in rubber mate- rial, galvanized material, weathering and corrosion of building material are some of the possible sources of heavy metal pollution in Peshawar. Peshawar can be considered as one big urban centre with high population and traffic density.